MOTIVASI KARYAWAN DITINJAU DARI GAYA KEPEMIMPINAN DEMOKRATIS - Krisna Putra Prayoga; Leonard Adrie Manafe (Universitas Linggabuana PGRI Sukabumi, 2023)
The goal of this study was to assess how the leadership style of CV.SENTRAL MAPAN personnel affects their performance. The methodology for this study is qualitative and descriptive. Researchers spoke with seven corporate employees who had been designated as research informants in order to gather preliminary data. The researcher also recorded some of the data and made firsthand observations in the field. The research's findings are based on the democratic leadership style exhibited by CV. SENTRAL MAPAN. In order to advance the company, company leaders have listened to employee criticism, recommendations, and opinions. They have also worked with employees to improve their performance. Company leaders regularly consult with employees before making decisions.